Promoting an educational and reflective space on health promotion and disease prevention practices - Germani, Alessandra (Guará Journal, 2018)
Scientific dissemination is the way to expand access to scientific knowledge for society as a whole, in order to help solve various social problems and bring the citizen closer to science. At the Federal University of Amapá-Unifap, there is a noticeable lack of dissemination of research. In this sense, we present the extension project Agency of Scientific Journalism, Science Unifap. The proposal developed a website with journalistic content involving the scientific and technological production of Unifap researchers. The project was developed based on research on strategies of scientif-ic dissemination in the field of public communication, the study of institutional production carried out by the communications sector of Unifap, as well as experiences in scientific dissemination by public institutions. The production of content took as a reference the specifics of webjournalism, especially the tendency to multi-media production, using accessible language, addressing issues of public interest.